Effect of type of starch on the starch aerogel incorporated with azadirachta indica - Kausalyaa Nanthakumar (2024)
The study addresses the impact of different types of starch on the properties of starch aerogels incorporated with Azadirachta Indica extract, with a focus on enhancing antimicrobial potency and sustainability in absorbent pads for food packaging. The problem statement revolves around the need to improve the antimicrobial efficacy and sustainability of absorbent pads in response to growing consumer demand for eco-friendly solutions. The objectives of the study are to investigate how different starch types influence aerogel characteristics on microstructure and extract retention within the aerogels. Methodologically, starch aerogels were synthesized via a sol-gel method, and plant extracts were extracted from Azadirachta Indica leaves. In starch aerogel, Azadirachta Indica extract was incorporated at 4 distinct concentrations (1wt.%, 2wt.%, 3wt.%, 4wt.%). As a control, a clean starch aerogel was also produced. The physical, chemical, mechanical, and biological properties of the aerogels are then evaluated. The antioxidant test revealed IC50 values of 32135.28, 64393.35, 96651.41, and 128909.48 μg/mL at neem extract concentrations of 500, 1000, 1500, and 2000 μg/mL, respectively. Water absorption capacity analysis showed that tapioca starch aerogels at 5 wt.% exhibited a total water absorption of 1.42% (control), while potato starch aerogels had a total water absorption of 1.06%. Increasing concentrations of neem extract led to higher water absorption percentages. Density tests indicated that aerogels containing 4% neem extract had the lowest densities. Optical microscopy revealed porous structures with hydrophilicity and highlighted the influence of starch type and neem extract concentration on microstructure. Furthermore, antimicrobial activity testing showed that tapioca starch exhibited a larger zone of inhibition against S. Aureus and E. coli compared to potato starch. Results indicate enhanced antimicrobial properties and improved characteristics of the aerogels, supporting the development of eco-friendly absorbent pads that align with consumer preferences for natural products and industry trends toward sustainability. Moreover, the findings contribute to addressing the pressing need for sustainable packaging solutions in the food industry, paving the way for the adoption of environmentally friendly absorbent pads in food packaging applications.